PENERAPAN BISNIS MODEL DENGAN PENDEKATAN BUSINESS MODEL CANVAS PADA INDUSTRI KECIL MENENGAH (Studi kasus di IKM QUE QOE di Kelurahan Tengah, Jakarta Timur) - Saragi Sitio, Vera Sylvia (JURNAL ILMIAH M-PROGRESS, 2017)
The government began focus their attention to the Small and Medium Industries (SMEs), because this sector can address equity in income distribution among other regions, which is the amount of labor absorption. SME QUE QOE is one of SMEs which is still surviving their business to compete with another enterpreuner. In order to resolve the problems which is faced by SMEs, this research focuses on the business canvas model (BMC). The aim of this research were to describe the business canvas model of SME QUE QOE and to know the desain of business canvas model as a form of business development strategies are appropriated and advised to apply at SME QUE QOE. This research is using method data which consists of qualitative methodological approach. The result of this research showed that SMEs have a great opportunity to develop their market with production registering such as PIRT and HALAL. Otherside, SMEs need to change packaging of their product so it can be marketable. Keywords : Business Canvas Model, Small and Medium Industries (SMEs)